Star of The Week Programs Based on Peer Relationship for Children Social Emotional Development - Suryana, Dadan; Khairma , Fitriana Sari; Sari, Novi Engla; Lina; Mayar, Farida; Satria, Sri (Jurnal Pendidikan Usia Dini, 2020)
The influence of family, school and peers on students' emotional social development is very important as a starting point for the design of school activities that will also improve student development in an integral way. The Star of the Week program was developed with the aim of helping students apply the knowledge, attitudes, and skills needed to socialize and understand and manage emotions. This study uses the Thiagarajan model stages, namely define, design, develop, and disseminate (4D). The results of the validity test from the experts show that this program has workable value with 91.1% material aspects, 90% emotional development aspects and 92% presentation aspects. For the practicality test results through teacher questionnaires obtained scores of 90%, and 88.67% through teacher observations of children who are in the high practical category. The results of the program effectiveness test showed a value of 89.08% on children's social-emotional development, because it showed an increase in values ​​before and after the intervention. The implication of further research is that it is hoped that various kinds of learning methods will develop aspects of child development based on cooperation and peer relationships. Keywords: Early Childhood, Peer Relationships, Star of the Week Program, Social Emotional References Acar, I. H., Hong, S. Y., & Wu, C. R. (2017). Examining the role of teacher presence and scaffolding in preschoolers’ peer interactions. European Early Childhood Education Research Journal, 25(6), 866–884. https://doi.org/10.1080/1350293X.2017.1380884 Acar, I. H., Rudasill, K. M., Molfese, V., Torquati, J., & Prokasky, A. (2015). Temperament and preschool children’s peer interactions. Early Education and Development, 26(4), 479–495. https://doi.org/10.1080/10409289.2015.1000718 Akhir, K., & Wisz, M. S. (2018). Sustainostic Nusantara : Managing marine plastic debris for sustainable tourism in the ‘ New Bali ’ of Indonesia (4.0). https://doi.org/https://doi.org/10.7287/peerj.preprints.26747v1 | Alwaely, S. A., Yousif, N. B. A., & Mikhaylov, A. (2020). Emotional development in preschoolers and socialization. Early Child Development and Care, 0(0), 1–10. https://doi.org/10.1080/03004430.2020.1717480 Asher, S. R., & Parker, J. G. (1989). Significance of Peer Relationship Problems in Childhood. In Social Competence in Developmental Perspective, 5–23. https://doi.org/https://doi.org/10.1007/978-94-009-2442-0_1 Beazidou, E., & Botsoglou, K. (2016). Peer acceptance and friendship in early childhood: the conceptual distinctions between them. Early Child Development and Care, 186(10), 1615–1631. https://doi.org/10.1080/03004430.2015.1117077 Blazevic, I. (2016). Family, Peer and School Influence on Children’s Social Development. World Journal of Education, 6(2), 42–49. https://doi.org/10.5430/wje.v6n2p42 Chung, K. K. H., Lam, C. B., & Liew, J. (2020). Studying Children’s Social-Emotional Development in School and at Home through a Cultural Lens. Early Education and Development, 31(6), 927–929. https://doi.org/10.1080/10409289.2020.1782860 Coelho, L., Torres, N., Fernandes, C., & Santos, A. J. (2017). Quality of play, social acceptance and reciprocal friendship in preschool children. European Early Childhood Education Research Journal, 25(6), 812–823. https://doi.org/10.1080/1350293X.2017.1380879 Conti-Ramsden, G., Mok, P., Durkin, K., Pickles, A., Toseeb, U., & Botting, N. (2019). Do emotional difficulties and peer problems occur together from childhood to adolescence? The case of children with a history of developmental language disorder (DLD). European Child and Adolescent Psychiatry, 28(7), 993–1004. https://doi.org/10.1007/s00787-018-1261-6 Di Maggio, R., Zappulla, C., Pace, U., & Izard, C. E. (2017). Adopting the Emotions Course in the Italian Context: A Pilot Study to Test Effects on Social-Emotional Competence in Preschool Children. Child Indicators Research, 10(2), 571–590. https://doi.org/10.1007/s12187-016-9387-x Domitrovich, C. E., Staley, K. C., Durlak, J. A., & Weissberg, R. P. (2017). Social-Emotional Competence : An Essential Factor for Promoting Positive Adjustment and Reducing Risk in School Children Social-Emotional Competence : An Essential Factor for Promoting Positive Adjustment and Reducing Risk in School Children. Child Development, 1–9. Durlak, J. A., Weissberg, R. P., Dymnicki, A. B., Taylor, R. D., & Schellinger, K. B. (2011). The Impact of Enhancing Students’ Social and Emotional Learning: A Meta-Analysis of School-Based Universal Interventions. Child Development, 82(1), 405–432. https://doi.org/10.1111/j.1467-8624.2010.01564.x Elias, M. J., & Haynes, N. M. (2008). Social Competence, Social Support, and Academic Achievement in Minority, Low-Income, Urban Elementary School Children. School Psychology Quarterly, 23(4), 474–495. https://doi.org/10.1037/1045-3830.23.4.474 Fajriyah, L. (2018). Pengembangan Literasi Emergen Pada Anak Usia Dini. Proceedings of the ICECRS, 165–172. https://doi.org/https://doi.org/10.21070/picecrs.v1i3.1394 Forrest, C. L., Gibson, J. L., Halligan, S. L., & St Clair, M. C. (2018). A longitudinal analysis of early language difficulty and peer problems on later emotional difficulties in adolescence: Evidence from the Millennium Cohort Study. Autism & Developmental Language Impairments, 3, 239694151879539. https://doi.org/10.1177/2396941518795392 Hartup, W. W. (1992). Peer Relations in Early and Middle Childhood. https://doi.org/https://doi.org/10.1007/978-1-4899-0694-6_11 Hernández, Y. C. U., Núñez, E. F. D., Inga-Arias, M., & Lozada, O. R. (2020). Early stimulation and emotional intelligence and its incidence in communication learning at the initial level. International Journal of Early Childhood Special Education,12(1), 433–441. https://doi.org/10.9756/INT-JECSE/V12I1.201023 Khoiruddin, M. A. (2018). Perkembangan Anak Ditinjau dari Kemampuan Sosial Emosional. Jurnal Pemikiran Keislaman, 29(2), 425–438. https://doi.org/https://doi.org/10.33367/tribakti.v29i2.624 Kim, J., & Cicchetti, D. (2010). Longitudinal pathways linking child maltreatment, emotion regulation. J Child Psychol Psychiatry, 51(6), 706–716. https://doi.org/10.1111/j.1469-7610.2009.02202.x.Longitudinal Kompri. (2016). Motivasi Pembelajaran Perspektif Guru dan Siswa. PT Remaja Rosdakarya. Krauthamer Ewing, E. S., Herres, J., Dilks, K. E., Rahim, F., & Trentacosta, C. J. (2019). Understanding of Emotions and Empathy: Predictors of Positive Parenting with Preschoolers in Economically Stressed Families. Journal of Child and Family Studies, 28(5), 1346–1358. https://doi.org/10.1007/s10826-018-01303-6 Lane, J. D., & Shepley, C. (2019). Research to Practice: Promoting Academic and Social Behaviors in a Small Group. Journal of Early Intervention, 41(4), 279–282. https://doi.org/10.1177/1053815116643833 Lojk, M., & Adolfsson, M. (2017). Promoting peer interactions of preschool children with behavior problems A Systematic Literature Review. Magdalena, S. M. (2013). Social and emotional competence - predictors of school adjustment. Procedia - Social and Behavioral Sciences, 76, 29–33. https://doi.org/10.1016/j.sbspro.2013.04.068 Maslow, A. (1984). Motivasi dan Kepribadian: Teori Motivasi dengan Ancangar Hirarki Kebutuhan Manusia. Gramedia Pustaka Utama. Mayar, F. (2013). Perkembangan Sosial Anak Usia Dini Sebagai Bibit Untuk Masa Depan Bangsa. AL-Ta Lim, 20(3), 459–464. https://doi.org/https://doi.org/10.15548/jt.v20i3.43 McCormac, M. E., & Snyder, S. (2019). Districtwide Initiative to Improve Tier 1 With Evidence-Based Classroom Lessons. Professional School Counseling, 22(1b), 2156759X1983443. https://doi.org/10.1177/2156759x19834438 Moberly, D. A., Waddle, J. L., & Duff, R. E. (2014). Journal of Early Childhood Teacher Education The use of rewards and punishment in early childhood classrooms The use of rewards and punishment in early childhood classrooms. Journal of Early Childhood Teacher Education, 37–41. https://doi.org/10.1080/1090102050250410 Moore, J. E., Cooper, B. R., Domitrovich, C. E., Morgan, N. R., Cleveland, M. J., Shah, H., Jacobson, L., & Greenberg, M. T. (2015). The effects of exposure to an enhanced preschool program on the social-emotional functioning of at-risk children. Early Childhood Research Quarterly, 32, 127–138. https://doi.org/10.1016/j.ecresq.2015.03.004 Morris, A. S., & Williamson, A. C. (2019). Building early social and emotional relationships with infants and toddlers: Integrating research and practice. Building Early Social and Emotional Relationships with Infants and Toddlers: Integrating Research and Practice, 1–351. https://doi.org/10.1007/978-3-030-03110-7 Morrison, G. S. (2012). Dasar-dasar Pendidikan Anak Usia Dini (PAUD). Indeks. Nix, R. L., Bierman, K. L., Domitrovich, C. E., & Gill, S. (2013). Promoting Children’s Social-Emotional Skills in Preschool Can Enhance Academic and Behavioral Functioning in Kindergarten: Findings from Head Start REDI. Early Educ Dev, 24(7), 1–7. https://doi.org/10.1080/10409289.2013.825565.Promoting Nurmalitasari, F. (2015). Perkembangan Sosial Emosi pada Anak Usia Prasekolah. Buletin Psikologi, 23(2), 103. https://doi.org/https://doi.org/10.22146/bpsi.10567 Ramani, G. B., Brownell, C. A., & Campbell, S. B. (2010). Positive and negative peer interaction in 3- and 4-year-olds in relation to regulation and dysregulation. In Journal of Genetic Psychology (Vol. 171, Issue 3). https://doi.org/10.1080/00221320903300353 Santrock, J. W. (2012). Perkembangan Masa Hidup. Erlangga. Shearer, R. J. B., Domínguez, X., Ell, E. R., Rouse, H. L., & Fantuzzo, J. W. (2010). Relation Between Behavioral Disorders Problems in Classroom Social and Learning Situations and Peer Social Competence in Head Start and kindergarten. Journal of Emotional and Behavioral Disorders, 18(4), 195–210. https://doi.org/https://doi.org/10.1177/1063426609351172 Uslu, F., & Gizir, S. (2017). School belonging of adolescents: The role of teacher–student relationships, peer relationships and family involvement. Kuram ve Uygulamada Egitim Bilimleri, 17(1), 63–82. https://doi.org/10.12738/estp.2017.1.0104 Wang, C., Hatzigianni, M., Shahaeian, A., Murray, E., & Harrison, L. J. (2016). The combined effects of teacher-child and peer relationships on children’s social-emotional adjustment. Journal of School Psychology, 59, 1–11. https://doi.org/10.1016/j.jsp.2016.09.003 Wang, Y., Palonen, T., Hurme, T. R., & Kinos, J. (2019). Do you want to play with me today? Friendship stability among preschool children. European Early Childhood Education Research Journal, 27(2), 170–184. https://doi.org/10.1080/1350293X.2019.1579545 Watanabe, N., Denham, S. A., Jones, N. M., Kobayashi, T., Bassett, H. H., & Ferrier, D. E. (2019). Working Toward Cross-Cultural Adaptation: Preliminary Psychometric Evaluation of the Affect Knowledge Test in Japanese Preschoolers. SAGE Open, 9(2), 2–4. https://doi.org/10.1177/2158244019846688 Westrupp, E. M., Reilly, S., McKean, C., Law, J., Mensah, F., & Nicholson, J. M. (2020). Vocabulary Development and Trajectories of Behavioral and Emotional Difficulties Via Academic Ability and Peer Problems. Child Development, 91(2), e365–e382. https://doi.org/10.1111/cdev.13219 Wilson, L. M., & Corpus, D. A. (2001). The Effects of Reward Systems on Academic Performance. Middle School Journal, 33(1), 56–60. https://doi.org/10.1080/00940771.2001.11495578 Yang, W., Datu, J. A. D., Lin, X., Lau, M. M., & Li, H. (2019). Can Early Childhood Curriculum Enhance Social-Emotional Competence in Low-Income Children? A Meta-Analysis of the Educational Effects. Early Education and Development,30(1), 36–59. https://doi.org/10.1080/10409289.2018.1539557